2019
DOI: 10.3390/w11040762
|View full text |Cite
|
Sign up to set email alerts
|

A Model Predictive Water-Level Difference Control Method for Automatic Control of Irrigation Canals

Abstract: In this paper, automatic control of the water level in an irrigation canal by automatic regulation of intermediate gates was studied. Previous scholars have proposed a water level difference control strategy that works to keep relative deviations in all pools the same for a particular situation where the operator does not have full control over the canal inflow, with the centralized linear quadratic regulator (LQR) control method used. While in practice, the deviation tolerance of pools may differ in some cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…Equations (14) and (15) are the control models in the form of state space equations for a single pool. The state space equations for a multi-pool canal can also be written in the form of Equations (14) and (15).…”
Section: Canal Control Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Equations (14) and (15) are the control models in the form of state space equations for a single pool. The state space equations for a multi-pool canal can also be written in the form of Equations (14) and (15).…”
Section: Canal Control Modelmentioning
confidence: 99%
“…The MPC strategy explicitly uses a simplified process model of the real system to determine control actions by minimizing an objective function. The aforementioned simplified control model with Equations (14) and (15) can be used as the process model. An output prediction is given by the process model.…”
Section: Mpc Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…Wahlin et al [27] found that combined feedforward-feedback controllers were better than either feedforward or feedback controllers alone. Kong et al [28] added a deviation weight coefficient into the algorithm for the middle route of the South-to-North Water Diversion Project, which could keep the water level deviations in all pools to certain proportions. However, these automatic control algorithms are incapable of dealing with the switching of working conditions and are rarely used in pumping stations.…”
Section: Introductionmentioning
confidence: 99%